Torsion of a Normal Ovary and Torsion of a Ovarian Tumor Two Different Unusual Cases - Çelik, Handan; Tosun, Migraci; Kefeli, Mehmet; Çetinkaya, Mehmet Bilge; Kökçü, Arif; Altunsoy, Süleyman; Güven, Davut (Gynecology Obstetrics & Reproductive Medicine, 2008)
Adnexal torsion is uncommon cause of severe abdominal pain in adolescents and postmenopausal women. We present two cases of ovarian torsion with two different etiologies in a 17-year-old adolescent girl with torsion of a normal ovary and 64 year-old postmenopausal woman with torsion of ovarian tumor. Most cases of ovarian torsion are due to some underlying ovarian pathology that causes ovary to twist around its vascular pedicle. In the first case, we present torsion of a normal ovary in an adolescent girl. Due to invasion or adherence to adjacent pelvic tissues, malignant ovarian tumors carry only 2% risk of torsion. In the second case, we report torsion of micropapillary type serous borderline ovarian tumor. It is important to keep ovarian torsion in mind in differential diagnosis in young adolescent girls and postmenopausal women with acute abdominal pain. Ultrasound with Doppler imaging is the main diagnostic tool with detailed history and physical exam. Once adnexal torsion is diagnosed, management is surgical. Further researches are necessary to develop methods of determining the viability of the ovary.